Cultural Diversity and Historical Traditions in Indonesia - Anindya Syifa Nuraini; Siti Nur Aprlianti; Tria Nur Erliani Agustin (HISTORICAL: Journal of History and Social Sciences, 2025)
This article reviews the history of tradition and culture in Indonesia, where this discussion is in the IPAS book grade III SD Curriculum Merdeka. This study aims to find out how the history of traditions and culture in Indonesia such as traditional ceremonies, traditional celebrations, performing arts, religious and various culinary specialties of each region. This research is a type of qualitative approach research, namely the study of information collection literature by examining sources related to diversity, tradition, culture, history of tradition, cultural history and preservation. The theory or basis for discussing this material is obtained from the results of obtaining information from many sources which use journals, ebooks, and articles. The results of the researcher's research, that it turns out that the history of tradition and culture in Indonesia is amazing because the country of Indonesia is a diverse country, with many differences such as religion, ethnicity, language, race, ethnicity, ethnicity and culture. This shows that the Indonesian state has a very rich cultural wealth, although with this much diversity it can cause division. However, the Indonesian state can handle it. This tradition in Indonesia is not only passed on to generations, but redeveloped by following the times. The history of this culture was influenced by kingdoms such as the Majapahit Kingdom and Srivijaya.